UPAYA GURU AL-QUR’AN DALAM MENINGKATKAN KEMAMPUAN MEMBACA AL-QUR’AN DENGAN METODE UMMI DI KELAS VI MI LITAHFIZHIL QUR’AN DARUSSALAM SENGKUBANG - Halidi, Halidi; Arnadi, Arnadi; Neli, Neli (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2024)
Madrasah Ibtidaiyyah Litahfizhil Qur'an Darussalam Sengkubang has attracted the interest of parents to be the main choice as an educational institution for their children at the basic education level, this is motivated by the use of the Qur'an learning method with the Ummi method applied. High public trust is certainly inseparable from the role of teachers who succeed in educating their students to be able to read, write and memorise the Qur'an properly. This study aims to reveal and analyse the efforts of al-Qur'an teachers in improving the ability to read the Qur'an with the Ummi method implemented at MI Litahfizhil Qur'an Darussalam Sengkubang. This research uses a qualitative approach and case study type. Data collection techniques were interviews, observation and documentation. Data analysis uses an interactive analysis model which includes data reduction, data display, and verification/conclusion drawing. The results showed that 1) The steps of the teacher in planning the learning of al-Qur'an Ummi method are guided by the rules set by the Ummi Foundation. 2) The teacher's process in implementing the learning of al-Qur'an Ummi method refers to the learning stages set by the Ummi Foundation and adds a slight variation to the implementation process. 3) Teacher techniques in evaluating learning Qur'an Ummi method refers to the evaluation techniques set by the Ummi Foundation. The application of the Ummi method by teachers in learning the Qur'an has a very good impact on students' ability to read the Qur'an.